(untitled) - Pushkarov, D. I. (Singapore, 1991)
This book is devoted to the development and application of the quasiparticle approach in the modern theory of solids in order to present some new results, ideas and phenomena. Considerable attention is paid to defects in quantum crystals.The volume, presenting a detailed discussion of quasiparticle mechanics and kinetics in nonstationary deformed solids, would be of particular interest to a wide class of specialists, lecturers and students in physics and mathematics.
Keywords: Nuclear physics,Quasiparticles (Physics),Vật lý nguyên tử,Quasiparticles (Vật lý)